Effectiveness of a Competency-based Foundation Course in Enriching Medical Education: Insights from First year MBBS Students - Ummay Kulsoom; Avantika Prakash; Aruna Nigam (Indian Journal of Medical Specialities)
Background: The medical profession requires extensive knowledge and skills, making it a demanding and challenging profession. To help 1st-year medical students from diverse cultural and social backgrounds transition from a highly protected school environment to a professional course, a 1-month orientation program has been introduced by the National Medical Council in India. Objectives: This study aimed to evaluate the feedback of 1st-year medical students on the competency-based medical education foundation course. Methodology: A cross-sectional study was conducted on 525 1st-year MBBS students from the 2022 to 2023 batch in various medical colleges across different states. A predesigned, structured, and validated questionnaire was used to obtain feedback from students on a 5-point Likert scale. Results: The feedback of 525 students was obtained and analyzed. The majority of students in all states reported 75%–100% orientation on the role of doctors in society, family practice, and national health policies. Basic life support skills were highly appreciated by most students (>55%) in all states. Computer skills were also found to be useful by the majority of students (61%). Most students (100%) reported sensitization and awareness of medical ethics and the availability of student support systems after attending the course. Field visits were rated as extremely useful, and the majority of students (52.9%) had exposure to sports and extracurricular activities. Conclusion: The foundation course aims to develop the necessary skills and leadership qualities that are essential for the overall development of an individual and an efficient doctor. Majority of the students rated the foundation course as very useful, indicating it to be a useful teaching program aiding in a smooth transition and adaptation to the various challenges throughout their professional course.